(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
In this article presents the materials of a prospective clinical and anamnestic analysis of children living in unfavorable and favorable areas of the studied region. A total of 50 children were examined, from 3 months to 5 years old. According to the results of the data obtained, acute obstructive bronchitis was most often found in children with aggravated anamneses, as well as in children often suffering from acute viral infections.